PEMILIHAN HARI PERNIKAHAN PADA TRADISI MAPPETTU ADA ADAT BUGIS DESA PUNGGUR PERSPEKTIF 'URF - Fajriyah, Nurul; Wagiyem, Wagiyem; Rahmiani, Nur (Al-Usroh, 2024)
This study aims to examine: 1) The philosophy of wedding day selection in the Mappettu Ada Bugis tradition of Punggur Village; 2) The practice of wedding day selection in this tradition; and 3) The 'Urf review of wedding day selection in this tradition. Employing a qualitative research method with a sociological approach, this research is a field study. Primary data were obtained through interviews with Bugis tribal leaders, Bugis community members, and religious leaders, while secondary data were sourced from relevant literature. Data analysis was conducted through data reduction, presentation, and verification, with data validity ensured through member checks and triangulation. The research results indicate that: 1) Wedding day selection in the Mappettu Ada tradition is usually done during the engagement period involving the family; 2) Village leaders in Punggur have various versions in determining the wedding day, either using hereditary books or the symbol of 'twelve stars'; 3) In the 'Urf review, this tradition can be classified as a valid 'urf if viewed as a form of effort, but it can become an invalid 'urf if linked to beliefs about safety or fate that contradict Islamic law.